Nitro-fatty acid formation and metabolism - Buchan, Gregory J. (2018)
Nitro-fatty acids (NO 2 -FA) are pleiotropic modulators of redox signaling pathways. Their effects on inflammatory signaling have been studied in great detail in cell, animal and clinical models primarily using exogenously administered nitro-oleic acid. While we know a considerable amount regarding NO 2 -FA signaling, endogenous formation and metabolism is relatively unexplored. This review will cover what is currently known regarding the proposed mechanisms of NO 2 -FA formation, dietary modulation of endogenous NO 2 -FA levels, pathways of NO 2 -FA metabolism and the detection of NO 2 -FA and corresponding metabolites.